Long-term predictions of the energy development-possibilities and challenges - Kanevche, Aleksandra; Dedinec, Aleksandar; Kanevce, Gligor; Kanevce, Ljubica (My University, 2016)
In this paper the possibilities, disadvantages, and benefits of long-term planning of energy development, are analysed. The factors influencing the development of energy and the factors influencing the accuracy of forecasting of the future development of energy are presented. The uncertainties that make the differences in modelling on a global scale, as well as the uncertainties that make the differences in modelling of the energy development of the Republic of Macedonia are also presented. Sensitivity analysis of the influence of different factors on the development of energy in the Republic of Macedonia was carried out. For those purposes the energy development of the Republic of Macedonia for the period up to 2035 year is calculated by using market allocation model. The main features of the market allocation model are also presented.
Keywords: energy development planning, market allocation, sensitivity analysis